2013
DOI: 10.1155/2013/213594
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Magnetic Dichroism in the Cobalt-Doped Indium Tin Oxide from First Principle Calculations

Abstract: The electronic structure of the Co-doped indium tin oxide (ITO) diluted magnetic semiconductors (DMSs) were investigated theoretically from first principles, using the fully relativistic Dirac linear muffin-tin orbital band structure method. The X-ray absorption spectra (XAS) and X-ray magnetic circular dichroism (XMCD) spectra at the CoL3, InM2, SnM2, and OKedges were investigated theoretically from first principles. The origin of the XMCD spectra in these compounds was examined. The calculated results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Instead, calculations indicate that ferromagnetism is related to defect concentration rather than TM ion doping [14]. In particular, oxygen vacancies may play an important role in the emergence of ferromagnetism in these materials [15,16]. Baqiah et al recently showed that the magnetic behavior of Codoped ITO films made by a sol-gel process was sensitive to both the Co doping concentration and the density of oxygen vacancies as well as the estimated ratio of oxygen defects to Co ions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, calculations indicate that ferromagnetism is related to defect concentration rather than TM ion doping [14]. In particular, oxygen vacancies may play an important role in the emergence of ferromagnetism in these materials [15,16]. Baqiah et al recently showed that the magnetic behavior of Codoped ITO films made by a sol-gel process was sensitive to both the Co doping concentration and the density of oxygen vacancies as well as the estimated ratio of oxygen defects to Co ions [17].…”
Section: Introductionmentioning
confidence: 99%